2014
DOI: 10.5539/ijbm.v9n4p173
|View full text |Cite
|
Sign up to set email alerts
|

Islamic Human Capital and Firm Performance: An Evidence of Small and Medium Enterprises in Bahrain

Abstract: This paper discusses on the human capital concept in Islamic perspectives and its relationship with business firm performance. There are emphases of Islamic principles on every well-known variables of human capital in conventional views. Muslims owner-managers seem to overlook and forget the importance and valuable elements of Islamic human capital which they rarely adopt in their business operations. Four variables of experience, motivation, business training and education are tested using the multiple regres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
7
0
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 42 publications
4
7
0
1
Order By: Relevance
“…The results of this study are consistent with the findings of Reuber and Fischer (1997), Athanassiou and Nigh (2002), Rafiki and Abdul-Wahab (2013) and Rafiki et al (2014) affirm the positive relationship between managers' experience and internationalisation.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…The results of this study are consistent with the findings of Reuber and Fischer (1997), Athanassiou and Nigh (2002), Rafiki and Abdul-Wahab (2013) and Rafiki et al (2014) affirm the positive relationship between managers' experience and internationalisation.…”
Section: Discussionsupporting
confidence: 92%
“…H3 Training positively influences family business internationalisation. The results of this study have also affirmed the findings of Carpenter and Fredrickson (2001), Rafiki and Abdul-Wahab (2013) and Rafiki et al (2014) of the positive relationship between training and internationalisation.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…The hypotheses that expected IHC to be positively related to market-based performance are supported for Islamic banks. These findings are in line with the previous research into the relationship between IHC and firms' market value (Boselie et al, 2001;Bosma et al, 2004;Colombo and Grilli, 2005;Nawaz, forthcoming;Rafiki et al, 2014;Subramaniam and Youndt, 2005). These findings indicate that the Islamic banking business model, which is based on ethical values defined by Shariah law, requires additional knowledge resources to interpret and employ Shariah in practice; therefore, these banks constantly invest in their human capital-base, which reflects positively on their market performance.…”
Section: Discussion Of Findingssupporting
confidence: 88%
“…Putri (2013) found that when employees can enhance their competences, success within an organisation is easily obtained, or in other words, organisational success is positively affected by human capital. Rafiki et al (2014) found that the growth and performance of an organisation can be influenced by Islamic human capital. Furthermore, a comprehensive approach that incorporates moral responsibility, skills and knowledge has been involved in Islamic human capital development.…”
Section: Financing Growth and Bmt Sustainabilitymentioning
confidence: 99%